Nicknames And Rememberance: Memorials To Woodlawn's Jazz Greats - Susan Olsen (Names, 2006)
Abstract In the world of jazz, musicians are known by their nicknames. “Duke,” “Bean,” “Cootie” are the names we recognize when we talk about the music made by Duke Ellington and his orchestra. The Woodlawn Cemetery in the Bronx is known worldwide as the final resting place of many jazz musicians, including Duke Ellington, Miles Davis, Coleman Hawkins, and Lionel Hampton. Although the nicknames of many members of the jazz community are incorporated into their gravemarkers, there are several musicians whose inscriptions record their legal names and make no reference to the nicknames connecting them to their careers. When a inscription is selected for a grave marker, it is permanent and shows how the purchaser of the memorial wants the individual to be remembered. In this essay, the resultant relationships among friends, family, and memorials is discussed.